2005
DOI: 10.1074/jbc.m412966200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phospholipase C-δ1 through Direct Interactions with the Small GTPase Ral and Calmodulin

Abstract: Second messengers generated from membrane lipids play a critical role in signaling and control diverse cellular processes. Despite being one of the most evolutionarily conserved of all the phosphoinositide-specific phospholipase C (PLC) isoforms, a family of enzymes responsible for hydrolysis of the membrane lipid phosphatidylinositol bisphosphate, the mechanism of PLC-␦1 activation is still poorly understood. Here we report a novel regulatory mechanism for PLC-␦1 activation that involves direct interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 52 publications
1
41
1
Order By: Relevance
“…We found that depletion of RalGDS also inhibits IP production of agonist-stimulated AT 1 R. This suggests that RalA activity is necessary for activation of PLC-␦1. This differs from the in vitro work of Sidhu et al (2005), who demonstrated that, similar to what is observed for Ral interactions with PLD, RalA interacts with PLC-␦1 irrespective of its GDP/GTP state (Luo et al, 1997(Luo et al, , 1998. Thus, we suggest that AT 1 R activation results in the ␤-arrestin-dependent translocation of RalGDS to the plasma, where it associates with the AT 1 R/RalA complex and promotes the RalA-dependent activation of PLC-␦1.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…We found that depletion of RalGDS also inhibits IP production of agonist-stimulated AT 1 R. This suggests that RalA activity is necessary for activation of PLC-␦1. This differs from the in vitro work of Sidhu et al (2005), who demonstrated that, similar to what is observed for Ral interactions with PLD, RalA interacts with PLC-␦1 irrespective of its GDP/GTP state (Luo et al, 1997(Luo et al, , 1998. Thus, we suggest that AT 1 R activation results in the ␤-arrestin-dependent translocation of RalGDS to the plasma, where it associates with the AT 1 R/RalA complex and promotes the RalA-dependent activation of PLC-␦1.…”
Section: Discussioncontrasting
confidence: 55%
“…The observation that siRNA-mediated knockdown of RalA significantly attenuates AT 1 R-mediated IP formation suggested that RalA coupled the receptor to an alternative PLC isoform. Sidhu et al (2005) reported that RalA interacted directly with PLC-␦1 and was sufficient to activate the phospholipase in vitro. Moreover, this effect of RalA was independent of the guanine nucleotide state of the GTPase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of the enzyme is increased with Ca 2ϩ elevations in the physiological range (33) but not by the G proteins that activate other PLCs (neither the heterotrimeric, nor the small forms). However, it was suggested that PLC␦1 is activated by the atypical G protein, transglutaminase II, or G␣H (429) or the small GTP binding protein RalA (515,1406). According to current views, PLC␦1 is regulated via its PH domain that recruits the enzyme to the PM.…”
Section: B Plc␦mentioning
confidence: 99%
“…To date, three Ral effectors have been identified: RalBP1 (6), the exocyst complex (7,8), and the ZonaB transcription factor (9). Both RalA and RalB also bind constitutively to phospholipase D1 and phospholipase C-d1 and are needed for their activation (10)(11)(12).…”
mentioning
confidence: 99%